Robust Tuning of PID Controller Using Differential Evolution Algorithm Based on FPGA - Yalcin, Ozan; Canli, Abdulkadir; Yilmaz, Ali Riza; Erkmen, Burcu (IEEE, 2022)
The development of technology has made control systems very important in the engineering world. The analysis and design of the controller/controller circuits that enable the systems to operate in the desired properties are among the main areas of control theory. In this study, the Proportional Integral Derivative (PID) controller is responsible for correcting the error that the Z-Source Inverter (ZSI) circuit receives from the difference between the input signal and the output signal. PID parameters are set by using the Differential Evolution Algorithm, one of the heuristic optimization algorithms. Thus, the most stable operation of the system is aimed. The model estimation has been made using Support Vector Regression (SVR) for a numeric cost function which is feasible for FPGA implementation. Differential Evolution Algorithm (DEA) has been implemented on FPGA due to its parallel processing capability. Despite the complexity of the algorithm with FPGA, the parameters are decided after 21.75 ms time.
Keywords: Differential Evolution Algorithm; FPGA; PID; Support Vector Regression; Z-Source Inverter; IMPLEMENTATION; Computer Science; Engineering